The impact of intelligent systems on management accounting - Marques, S.; Gonçalves, R.; Lopes da Costa, R.; Pereira, L.; Dias, Á. (International Journal of Intelligent Information Technologies, 2023)
In today's competitive and changing business environment, the concern about technologies and intelligent systems has gained more notoriety. However, companies still have many tasks performed by humans; in the medium-term, intelligent systems will become more present in companies and will perform tasks that are currently done by humans much more efficiently. There is a need for companies to adapt and to start thinking about combining human and intelligent systems capabilities. This research was focused specifically in the management accounting profession, as these professionals spend a lot of time collecting and organizing data, doing repetitive tasks that can be easily and quickly accomplished by intelligent systems. This research studied the impact that artificial intelligence, big data, and internet of things can have in this profession.